Dual action of leucocyte dialysates and of thymosin on the recovery of sheep-cell-rosetting capacity in trypsinized human lymphocytes. - Sargent, I L (1982)
Trypsinization of human blood lymphocytes abolishes their capacity to form rosettes with sheep erythrocytes (E-rosettes) and this is regained in part on incubation of the cells at 37 degrees C for 3 hr. The recovery of rosetting capacity was found to be accelerated in the presence of dialysable extracts of human leucocytes (DLE) or bovine thymosin fraction 5 (THFV). For both DLE and THFV two types of effect were demonstrated. At lower concentrations the stimulation of recovery was dependent on the presence of the agent during incubation and it presumably comes about through an effect on the metabolic process required for regeneration of the E-receptors. At higher concentrations another mechanism is apparent since the agents were now effective when added after incubation. This last phenomenon is wholly dependent on prior incubation of the trypsinized lymphocytes in medium alone and it probably involves attachment of components of DLE and THFV to incompletely recovered cells, thereby providing a more favourable charge environment for E-rosette formation. A similar process of adhesion-promotion may be occurring in certain in-vitro tests with THFV which are carried out on lymphocytes from immunodeficient patients. On the other hand, it is the other mechanism, that of metabolic action, which is likely to be the predominant consideration in relation to treatment of such patients with DLE or THFV.